A First Step to a Biomarker of Curative Surgery in Colorectal Cancer by Liquid Biopsy of Methylated Septin 9 Gene. (5th June 2020) - Leon Arellano, M.; García-Arranz, M.; Ruiz, R.; Olivera, R.; Magallares, S.; Olmedillas-Lopez, S.; Valdes-Sanchez, T.; Guadalajara, H.; García-Olmo, D.
Abstract : Objectives . To confirm that patients affected by colorectal cancer have the V2 region of Septin 9 ( SEPT9 ) gene hypermethylated in the circulating free DNA from a peripheral blood sample before surgery and to determine if this hypermethylated DNA disappears from the patients after complete resection of the tumour. Methods . Plasma from 10 patients with colorectal cancer was collected preoperative and three months after surgery. The analysis of the methylation status of the promoter region of the SEPT9 gene was performed using a 7500 Fast Real-Time PCR System. Results . Hypermethylation of SEPT9 gene was detected in 8 out of 10 preoperative samples (one negative result was probed to be a Lynch syndrome) and in 4 out of 10 postoperative samples matching with the cases of recurrence or persistence of disease. This means that, in this sample, the preoperative sensitivity and specificity of the test were 88.9% and 100%, respectively, and there is 100% correlation between the positive results of the SEPT9 test and a recurrence/persistence of the disease in patients after surgical resection. Conclusions . Our study shows that circulating hypermethylated SEPT9 is a specific colorectal cancer biomarker. This hypermethylated SEPT9 DNA disappears around three months after surgery and that circulating hypermethylated SEPT9 may be the first noninvasive marker for postsurgical diagnosis; this conclusion must be confirmed with a more significant number of patients.